2020
DOI: 10.1177/0363546520914936
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Bone–Patellar Tendon–Bone Anterior Cruciate Ligament Reconstruction With and Without Lateral Extra-articular Tenodesis: 19-Year Clinical and Radiological Follow-up

Abstract: Background: Arthroscopic anterior cruciate ligament (ACL) reconstruction (ACLR) with a bone–patellar tendon–bone graft (BTB) is a reliable surgical option for the control of anterior knee laxity after ACL injury. The addition of a lateral extra-articular tenodesis (LET) may improve control of rotation knee laxity and improve short-term graft survival in high-risk patients. Purpose: The aims of this study were to compare long-term patient-reported outcomes, graft survival, and risk of osteoarthritis between ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 35 publications
5
109
0
3
Order By: Relevance
“…Titles and abstracts were reviewed, and the full text of 31 articles was examined. Ultimately, 6 RCTs 4,8,18,45,46,51 were included in this review (Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Titles and abstracts were reviewed, and the full text of 31 articles was examined. Ultimately, 6 RCTs 4,8,18,45,46,51 were included in this review (Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…Results from the quality assessment of included studies are summarized in Figure 3. One study 8 was rated as having a high risk of selection bias because it reported unblinded block randomization for group allocation. Also, 2 studies 46,51 reported that participants were allocated randomly but did not adequately describe the randomization method, thus resulting in an unclear risk of bias rating.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the important long-term findings include greater allograft failures compared with autografts 21 and high incidence of osteoarthritic changes in reconstructed knees ranging from 22% to 100%. [60][61][62][63][64][65] There were no significant differences in…”
Section: Long-term Follow Up Rcts ( ‡10 Years)mentioning
confidence: 83%
“…outcomes reported between bioabsorbable or metal screws for graft fixation, 66 patellar versus hamstrings, 62,63,[67][68][69] open versus arthroscopic, 61 or singleversus double-bundle reconstructions 65 (Table 5). 21,40,[59][60][61][62][63][64][65][66][67][68][69][70][71]…”
Section: Long-term Follow Up Rcts ( ‡10 Years)mentioning
confidence: 99%